Wood density proxies of adaptive traits linked with resistance to drought in Douglas fir (Pseudotsuga menziesii (Mirb.) Franco) - Ruiz Diaz Britez, Manuela; Sergent, Anne Sophie; Martinez Meier, Alejandro; Bréda, Nathalie; Rozenberg, Philippe (Springer, 2018)
A comparison of dead and surviving Douglas fir trees following the 2003 drought was made to define proxies of adaptive traits for resistance to drought. Increment cores were sampled from trees from three French regions: Centre, Midi-Pyrénées and Burgundy. Original tree-ring variables were calculated, based on a sliding density criterion dividing the microdensity profile into high- and low-density segments. Tree rings were analysed at each site in a number of consecutive annual rings before the 2003 drought event. Comparison between pairs of surviving and dead trees and between pairs of randomly selected trees (whether dead or alive) supports the evidence of systematic dissimilarities between surviving and dead trees in a number of original density variables. Correlation analysis between original and conventional ring density variables indicates a weak association. We found that the surviving trees were denser than the dead trees in all three sites, but that the denser part of the ring varied from region to region. We identified several original density variables intended to be used as proxies of adaptive traits in future studies of genetic determinism of Douglas fir resistance to drought.